The Tenets of Jihād and Takfīr in the Emerging Concept of Wasaṭīya (Moderation) as Counterterrorism in Saudi Arabia. Issue 3 (3rd July 2019) - Nakamura, Satoru
Abstract: A large-scale research project on wasaṭīya (the political positioning of parties and factions in the centre, which is translated as moderation in Saudi Arabia) was initiated in King Saud University in 2009, and resulted in the publishing of the Encyclopedia of Wasaṭīya in 2015 as a six-volume series. This national challenge in Saudi Arabia adopted methodology enabling Muslims to form a reliable understanding of the Qurʾan verses and the Sunna of the Prophet Muḥammad, resulting in research conclusions that limit jihād for defensive motivations, advocate judgements of excommunication with deliberation, and separate the Sunna from terrorist approaches. This emerging concept of wasaṭīya is the historical outcome of the de-politicised Salafism nurtured in Saudi Arabian political history.